Spectacular Blindness: Enslaved Children and African Artifacts in Eighteenth-Century Paris - Étienne, Noémie; Martin, Meredith (Status Quaestionis, 2025)
In this essay we explore the presence and display of African children and artifacts in eighteenth-century Paris via their visual, material, and textual traces. While considering how such traces can help conjure or visualize human lives and ephemeral events, we also probe a paradox we call ‘spectacular blindness’. Although individuals and artifacts of African descent were conspicuously visible at the French court, they were rarely fully seen – and, in the case of enslaved children, their subjectivity and the trauma they experienced were seldom acknowledged. We argue that the pervasive visibility of these individuals paradoxically made their humanity invisible to enslavers or turned that humanity into a tool for elite white self-expression and domination. Constantly put on display, they became spectacular blind spots, and, until recently, they have also been absent from most art historical narratives. Even today, their existence and portrayal can be met with disavowal and silence.